Gambaran Kesejahteraan Spiritual pada Pasien Kanker Payudara - Nurul Nisah; Miftahul Raudhah (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2026)
Breast cancer is a chronic disease that affects not only physical health but also psychological, social, and spiritual aspects of patients’ lives. Spiritual well-being is an important internal resource that helps patients cope with illness, maintain hope, and find meaning in life during long-term treatment. This study aimed to describe the level of spiritual well-being among breast cancer patients undergoing treatment. This research employed a quantitative descriptive design with a cross-sectional approach. A total of 142 breast cancer patients were selected using purposive sampling at the Oncology Center of RSUD dr. Zainoel Abidin Banda Aceh. Data were collected using the Spiritual Well-Being Scale (SWBS), which measures religious and existential well-being, and were analyzed descriptively. The results showed that the majority of respondents had a high level of spiritual well-being (66.2%), while 23.9% were categorized as moderate and 9.9% as low. These findings indicate that breast cancer patients generally have strong spiritual resources, particularly in maintaining their relationship with God and finding meaning and purpose in life despite living with a chronic illness. This study highlights the importance of integrating spiritual assessment and spiritual care into holistic nursing practice, especially in palliative and supportive care settings.